2023
DOI: 10.1021/acs.nanolett.3c02483
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Chirality-Induced Spin Selective Quantum Capacitance in α-Helical Peptides

Pius Markus Theiler,
Christian Ritz,
Raphael Hofmann
et al.

Abstract: Advanced Kelvin probe force microscopy simultaneously detects the quantum capacitance and surface potential of an α-helical peptide monolayer. These indicators shift when either the magnetic polarization or the enantiomer is toggled. A model based on a triangular quantum well in thermal and chemical equilibrium and electron–electron interactions allows for calculating the electrical potential profile from the measured data. The combination of the model and the measurements shows that no global charge transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…DNA (see refs , , , , , , , ) and α-helical oligopeptides (see refs , , , , , , , , , , , , , , , , , ) have been widely used to explore the CISS effect and its connection with molecular properties. Having been investigated by spin-dependent photoemission, transport, electrochemical, and spin-dependent polarization experiments, they comprise testbed systems for comparisons between methods.…”
Section: Materials and Molecules Exhibiting Cissmentioning
confidence: 99%
“…DNA (see refs , , , , , , , ) and α-helical oligopeptides (see refs , , , , , , , , , , , , , , , , , ) have been widely used to explore the CISS effect and its connection with molecular properties. Having been investigated by spin-dependent photoemission, transport, electrochemical, and spin-dependent polarization experiments, they comprise testbed systems for comparisons between methods.…”
Section: Materials and Molecules Exhibiting Cissmentioning
confidence: 99%
“…Recent experimental results report a modification of the (electrostatic) equilibrium properties of a chiral system coupled to a ferromagnet in the absence of a bias current. It was found that the contact potential of chiral molecules on a ferromagnet is modified either by reversal of the magnetization direction or by interchanging the chirality of the system. Theiler et al recently reported a shift of the contact potential measured by Kelvin probe force microscopy (KPFM) of 50 mV when the direction of the magnetization is reversed, which is similar in magnitude to the values previously reported by KPFM measurements and photoemission experiments . We note that no electron transport is involved in these measurements of the contact potential shifts.…”
Section: Magnetochiral Contact Potential Modificationmentioning
confidence: 99%
“…To check the feasibility of this mechanism, we calculate the areal electron density, N , that is required to build up a potential difference of Δψ ⇆ = 50 mV over a typical length scale of a molecule d = 1 nm, using a parallel plate capacitor approximation, N = ϵ s normalΔ ψ false⇆ e d where ϵ s = ϵ r ϵ 0 is the permittivity and e is the electron charge. With ϵ r = 5, we find that N = 10 –2 nm –2 , which corresponds to 2.5 × 10 –3 electron charge per molecule for a molecular packing density of 4 nm –2 .…”
Section: Magnetochiral Contact Potential Modificationmentioning
confidence: 99%
See 2 more Smart Citations